Successful Novel Treatment of Granuloma Faciale Using CO2 Emulated Er:YAG Laser Ablation. Issue 10 (7th October 2021) - Bayne, Kilee; Fornwalt, Brandon E.; Jonda, Christopher F.; Cash, Adam D.
Abstract : Summary: Granuloma faciale is a rare, benign inflammatory skin disease that has multiple medical treatment modalities due to its frequent unresponsiveness to treatment. This skin disease presents as a single, well-demarcated red-brown to violaceous, raised lesion, most commonly on the face, in middle-aged White men. Its etiology is unknown; sun exposure is thought to have some implications in its formation. Treatment modalities for granuloma faciale include topical therapy, intralesional injections, systemic therapies, phototherapy, lasers, cryotherapy, and surgical excision. In this article, we will highlight a rare case of granuloma faciale and its novel and successful treatment with a carbon dioxide emulated Er:YAG laser.